Clostridioides difficile in the environment, food, animals and humans in southern Italy: Occurrence and genetic relatedness. (August 2018) - Romano, Vincenza; Pasquale, Vincenzo; Lemee, Ludovic; El Meouche, Imane; Pestel-Caron, Martine; Capuano, Federico; Buono, Pasqualina; Dumontet, Stefano
Highlights: Clostridioides difficile was isolated from environment, food, animals and humans. The most common PCR ribotypes were 126, 078, 011/018, 014/020/077, and 010. Toxigenic strains were isolated from bovine raw milk and ready-to-eat vegetable samples. MLVA showed that many isolates from different sources were genetically undistinguishable. Environment, food and animals could be important sources of virulent C. difficile strains. Abstract: One hundred and thirty-eight C. difficile isolates from different sources (66 from the environment, 36 from animals, 9 from food and 27 from humans) were ribotyped by capillary electrophoresis PCR ribotyping (CE-PCR). A multilocus variable tandem repeat analysis (MLVA) was carried out on a sample subset. The most frequently isolated PCR ribotypes were 126 (15.9%), 078 (14.5%), 011/018 (11.6%), 014/020/077 (10.1%), and 010 (2.8%). In particular, strains of PCR ribotype 011/018 were isolated from human, raw milk and environmental samples. The hypervirulent PCR ribotype 027 was isolated from two human samples. The majority of the strains were toxigenic (34.1% showed the toxigenic profile A + B + CDT + and 38.9% the profile A + B + CDT − ). MLVA allowed to identify 4 clonal complexes of genetically related isolates: complex n. 1 grouped together human, environmental and food strains, whereas complex n. 3 included human and environmental isolates. The use of MLVA gave further evidence to the possible role of environment, animals and food as routes of transmission of C. difficile infections to human.